Blood Transfusion and Risk of Venous Thromboembolism: A Population-Based Cohort Study - Lin, Shih-Yi; Chang, Yun-Lung; Yeh, Hung-Chieh; Lin, Cheng-Li; Kao, Chia-Hung (Thrombosis and Haemostasis, 2020)
Background The risk of venous thromboembolism (VTE) in generally ill patients, both under outpatient and inpatient care, following blood transfusion has not been determined.Methods This retrospective population-based cohort study was conducted using the National Health Insurance Research Database. We studied patients who received blood transfusion, defined as red blood cell transfusion of any type, from January 1, 2000 to December 31, 2011. The index date was defined as the date of blood transfusion. The primary outcome was VTE. Propensity score matching and Cox proportional hazard models were used.Results A total of 41,866 patients who underwent blood transfusion and 41,866 matched controls were studied. Generally, the blood transfusion cohort has 2.98 times higher risk of VTE than the control cohort (95% confidence interval [CI] = 1.23–7.22). The blood transfusion cohort had respectively 1.99 and 1.64 times higher risk of deep vein thrombosis (DVT) and pulmonary embolism (PE) compared with the control cohort (DVT, 95% CI = 1.65–2.41; PE, 95% CI = 1.19–2.26). Patients in the blood transfusion cohort who did not use warfarin were 1.95 times more likely to develop VTE than those in the control cohort (adjusted hazard ratio [HR]: 1.95, 95% CI = 1.65–2.31). Patients in the blood transfusion cohort were 1.74 times more likely to die than those in the control cohort (adjusted HR: 1.74, 95% CI = 1.48–2.05).Conclusion Blood transfusion is associated with an increased risk of VTE. The risk of VTE decreased in those who took warfarin.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; blood transfusion